2019
DOI: 10.1111/jce.14050
|View full text |Cite
|
Sign up to set email alerts
|

Management of acute cardiac tamponade by direct autologous blood transfusion in interventional electrophysiology

Abstract: Aims: Acute cardiac tamponade (ACT) is the most common life-threatening complication of interventional electrophysiology. Urgent drainage by percutaneous pericardiocentesis and anticoagulation reversal are required. Immediate direct transfusion of the blood volume aspirated from the pericardial space to the patient has been rarely described. This study was designed to assess the efficacy and safety of immediate direct autologous blood transfusion (AutoBT).Methods: A retrospective case series of direct AutoBT p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…However, DAT has not been routinely adopted by most interventional electrophysiologists due to its potential risks of thrombotic and infective events. Recently, two studies (10,11) preliminary investigated the feasibility of DAT in APT during the perioperative period of EP procedures and revealed that DAT reduced the need for allotransfusion and surgical repair without increasing major complications. However, among different EP procedures, only a few (<10) AF patients were enrolled in either study, therefore, their conclusions cannot be completely applicable for AF-CA and need to be further explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, DAT has not been routinely adopted by most interventional electrophysiologists due to its potential risks of thrombotic and infective events. Recently, two studies (10,11) preliminary investigated the feasibility of DAT in APT during the perioperative period of EP procedures and revealed that DAT reduced the need for allotransfusion and surgical repair without increasing major complications. However, among different EP procedures, only a few (<10) AF patients were enrolled in either study, therefore, their conclusions cannot be completely applicable for AF-CA and need to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Direct autotransfusion (DAT), a method of reinjecting aspirated pericardial blood directly back into the body via venous access without a cell-salvage system, may be easy to operate and can quickly stabilize hemodynamic status and buy time for anticoagulation reversal or cardiac surgical repair. Previous studies had reported cases of applying DAT to deal with APT during the perioperative period of AF-CA (9)(10)(11)(12)(13). However, despite the many potential advantages, DAT has not been conventionally adopted yet, due to the lack of consensus on security.…”
Section: Introductionmentioning
confidence: 99%
“…Protamine was administered in 14 patients for periprocedural heparin reversal. Direct autologous blood transfusion (AutoBT) was performed routinely as salvage therapy to allow maintenance the hemodynamic status (13). Despite pericardiocentesis, anticoagulation reversal, and AutoBT, an emergent open-chest surgery was required in 11 (52.4%) patients due to persistent reaccumulation of blood in the pericardial space.…”
Section: Bleeding Complicationsmentioning
confidence: 99%
“…Percutaneous cardiac interventions are increasingly utilized with varying procedure complexity and ongoing technological innovations 1 . Specific steps during procedures (e.g., transseptal puncture) increase the risk of developing pericardial effusion, which may then lead to cardiac tamponade (CT) 2 . Coronary interventional (CI) procedures and complications like guidewire‐related coronary perforation, intracoronary balloon rupture, and atherectomy device‐related rupture can lead to pericardial effusion and CT, requiring acute, life‐saving intervention 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“… 1 Specific steps during procedures (e.g., transseptal puncture) increase the risk of developing pericardial effusion, which may then lead to cardiac tamponade (CT). 2 Coronary interventional (CI) procedures and complications like guidewire‐related coronary perforation, intracoronary balloon rupture, and atherectomy device‐related rupture can lead to pericardial effusion and CT, requiring acute, life‐saving intervention. 3 , 4 Electrophysiology procedures (EP), such as device implantations (including left atrial appendage occlusion [LAAO]) and ablation procedures may also be complicated by pericardial effusion and CT. 5 Most EP procedures are performed using venous access (low pressure), except ablations done in the left atrium or left ventricle, whereas coronary interventional procedures generally involve the arterial (high pressure) side of the circulation.…”
Section: Introductionmentioning
confidence: 99%